From Physiological to Moral Disgust: a Possible Fruition (Itinera, 2019)
Through the aesthetic and cinematographic analysis of the film The Elephant Man by David Lynch it is shown how the relationship between physiological and moral disgust allows an aesthetic fruition of disgust. By focusing attention on the specific characteristics and laws that regulate disgust, it will be possible to observe how an aesthetic appreciation of disgust is possible, highlighting the problems that it implies.